Reality behind the Vietnam Refugees in Viet Thanh Nguyen's the Sympathizer - Chandran, Kavya (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This article deals with the reasons behind the Indo-china war and the emergence of Vietnamese refugees. Nguyen was a Vietnamese American writer who writes in the themes of political manifestation, communism, colonialism, migration, racial discrimination, memories, and nostalgia. He discusses about how the French colonization ended in the separation of the Vietnam, the political influence in the emergence of Vietnam War and the refugee life in America. Here in this article I tried to point out that the refugees like any other creatures, cannot survive without freedom, stability and the acceptance from the foreign land.
Keywords: Colonialism; Communism; Migration; Political manifesto; war